Tanggung Jawab Notaris Terhadap Akta Nominee dalam Jual Beli Tanah (Studi Kasus Putusan Mahkamah Agung Nomor 1290 K/Pdt/2022) - Ade Putra Prima; Busyra Azheri; Yussy Adelina Mannas (LPPM Universitas Ekasakti Padang, 2023)
The practice of nominee agreements is related to the principle of justice considering the interests of the parties involved. The nominee agreement is intended to provide all the authority that may arise in a legal relationship between the authorizing parties over a plot of land which according to land law cannot be owned by a foreign party which is then given to the indigenous people as the beneficiary. The notary as a public official is required to be responsible for the deed he made.